Color Storytelling Sebagai Visual Narrative Pada Film Animasi The Red Turtle - Zahra Salsabila; Dini Faisal (Universitas Katolik Widya Karya Malang, 2023)
The Red Turtle is an animated film released in 2016. It was directed by Dutch-British animator Michall Dudok de Wit. The film is a co-production between Wild Bunch and Studio Ghibli. The Red Turtle tells of the struggle of a man stranded on an uninhabited island to survive until he finally finds new happiness on the island. The film